The Effect Of Work Motivation And Work Discipline On Employee Performance At The South Kikim Sub-District Office - Esti Kinanti; M. Pahlan; Kasinem Kasinem (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of work motivation and work discipline on employee performance at the Kikim Selatan District Office. The method used is descriptive quantitative. The population in this study consists of all employees at the Kikim Selatan District Office, with a total of 38 respondents taken through a census method, in which the entire population is used as the sample. Data were collected through questionnaires and analyzed using statistical calculations with multiple linear regression, validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, descriptive statistical test, partial test (t-test), simultaneous test (f-test), and coefficient of determination test. The results show that work motivation does not affect employee performance. Work discipline has a positive and significant effect on employee performance. Work motivation and work discipline together significantly influence employee performance, meaning that increasing work motivation and work discipline can improve employee performance in the Kikim Selatan District Office.